Intravenous N‐acetylcysteine in pediatric patients with nonacetaminophen acute liver failure: A placebo‐controlled clinical trial12. Issue 4 (4th February 2013) - Squires, Robert H.; Dhawan, Anil; Alonso, Estella; Narkewicz, Michael R.; Shneider, Benjamin L.; Rodriguez‐Baez, Norberto; Olio, Dominic Dell; Karpen, Saul; Bucuvalas, John; Lobritto, Steven; Rand, Elizabeth; Rosenthal, Philip; et al.
Abstract N‐acetylcysteine (NAC) was found to improve transplantation‐free survival in only those adults with nonacetaminophen (non‐APAP) acute liver failure (ALF) and grade 1‐2 hepatic encephalopathy (HE). Because non‐APAP ALF differs significantly between children and adults, the Pediatric Acute Liver Failure (PALF) Study Group evaluated NAC in non‐APAP PALF. Children from birth through age 17 years with non‐APAP ALF enrolled in the PALF registry were eligible to enter an adaptively allocated, doubly masked, placebo‐controlled trial using a continuous intravenous infusion of NAC (150 mg/kg/day in 5% dextrose in water [D5W]) or placebo (D5W) for up to 7 days. The primary outcome was 1‐year survival. Secondary outcomes included liver transplantation‐free survival, liver transplantation (LTx), length of intensive care unit (ICU) and hospital stays, organ system failure, and maximum HE score. A total of 184 participants were enrolled in the trial with 92 in each arm. The 1‐year survival did not differ significantly (P = 0.19) between the NAC (73%) and placebo (82%) treatment groups. The 1‐year LTx‐free survival was significantly lower (P = 0.03) in those who received NAC (35%) than those who received placebo (53%), particularly, but not significantly so, among those less than 2 years old with HE grade 0‐1 (NAC 25%; placebo 60%; P = 0.0493). There were no significant differences between treatment arms for hospital or ICU length of stay, organ systems failing, or highest recorded grade of HE. Conclusion: NAC did not improve 1‐year survival in non‐APAP PALF. One‐year LTx‐free survival was significantly lower with NAC, particularly among those <2 years old. These results do not support broad use of NAC in non‐APAP PALF and emphasizes the importance of conducting controlled pediatric drug trials, regardless of results in adults. (HEPATOLOGY 2013)